HUBUNGAN KARAKTERISTIK DEMOGRAFI DENGAN KEJADIAN DISMINORE PADA WANITA USIA SUBUR DI DESA SIHONONGAN KECAMATAN PARANGINAN KABUPATEN HUMBANG HASUNDUTAN TAHUN 2022 - Lilis Novitarum,; Imelda Derang,; Ester Sianturi, (Jurnal Cakrawala Ilmiah, 2023)
Every month women will experience menstruation, most women experience dysmenorrhea women who have an menarche age will have an impact on the incidence of dysmenorrhea and women must maintain nutritional status. This study aims to determine the relationship between demographic characteristics and the incidence of dysmenorrhea in women of childbearing age at Sihonongan Village, Paranginan District, Humbang Hasundutan Regency 2022. This type of research used a cross sectional design. The sampling technique use purposive sampling, totaling 90 respondents. The instrument used is a demographic characteristics questionnaire and a dysmenorrhea questionnaire. The results showed that the family history is 65.6%, nutritional status show good category 90% and the incidence of dysmenorrhea was 86.7%. Based on the results of the Fisher exact test statistical test, age is not associated with the incidence of dysmenorrhea, the p-value is 0.867 (>0.05), family history is associated with the incidence of dysmenorrhea, the p-value is 0.006 (<0.05), nutritional status is not associated with the incidence of dysmenorrhea obtained p-value 0.343 (> 0.05). It is recommended for women of childbearing age to pay more attention to nutritional status such as consuming fruits and vegetables that are high in vitamins, protein, and carbohydrates and drinking enough water.